1999
DOI: 10.1262/jrd.45.29
|View full text |Cite
|
Sign up to set email alerts
|

Production of Transgenic Rats and Mice by the Testis-Mediated Gene Transfer

Abstract: Abstract. Recent reports have shown that sperm cells incubated with foreign DNA in vitro are able to transfer the DNA into eggs at fertilization. The present study examined if an injection of DNA into the testis in vivo could generate transgenic animals via sperm ejaculated. We prepared 3 gene constructs; human growth hormone (hGH), hGH receptor (hGHR) and mouse leptin (mOB) genes fused to the promoter regions of the mouse genes for whey acidic protein (WAP), metallothionein-I (MT) and mouse mammary tumor viru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
1

Year Published

1999
1999
2009
2009

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 40 publications
(52 reference statements)
1
19
1
Order By: Relevance
“…The percentage of transgenic pups thus generated (3 out of 17 for one construct and 2 out of 36 for another one) was in the range of that obtained by DNA microinjection and comparable to that obtained in mice (Chang et al, 1999). In vivo electroporation of DNA into mouse testes has been described (Celebi et al, 2003), however, no reports on the use of this or other gene transfer techniques or vectors in rat testes have been published (Wall, 2002;Celebi et al, 2003).…”
Section: C) Sperm-mediated Transgenesissupporting
confidence: 54%
See 1 more Smart Citation
“…The percentage of transgenic pups thus generated (3 out of 17 for one construct and 2 out of 36 for another one) was in the range of that obtained by DNA microinjection and comparable to that obtained in mice (Chang et al, 1999). In vivo electroporation of DNA into mouse testes has been described (Celebi et al, 2003), however, no reports on the use of this or other gene transfer techniques or vectors in rat testes have been published (Wall, 2002;Celebi et al, 2003).…”
Section: C) Sperm-mediated Transgenesissupporting
confidence: 54%
“…Transgenic rats have been generated by germline gene transfer through injection of plasmid DNA-liposome complexes into the seminiferous tubules of male rats and subsequent mating of these males with wild-type females (Chang et al, 1999). The percentage of transgenic pups thus generated (3 out of 17 for one construct and 2 out of 36 for another one) was in the range of that obtained by DNA microinjection and comparable to that obtained in mice (Chang et al, 1999).…”
Section: C) Sperm-mediated Transgenesismentioning
confidence: 82%
“…The fusion gene construct of mouse metallothionein-I promoter (MT)/human growth hormone receptor (hGHR) was prepared as described in the associated paper [18]. The DNA construct labeled with FITC was prepared by Sawady Technology (Tokyo) by PCR using this MT/hGHR gene as a template with primers labeled with FITC at their 5'-ends.…”
Section: Detection Of Injected Dna In Epididymal Spermatozoamentioning
confidence: 99%
“…These studies have facilitated the idea of using sperm as a vector to transfer exoge-actually carry the DNA into eggs, and the gene thus transferred is transcriptionally active [11][12][13][14][15][16][17]. In addition, as described in the associated paper [18], we have shown that DNAs injected into the testis of either rats or mice can be transferred into eggs via sperm at fertilization (testis-mediated gene transfer). The transgenes could be expressed and transmitted in the descendants, suggesting that injected DNAs were stably integrated in the genome of offspring.…”
mentioning
confidence: 95%
“…2005). A perspective modification of this technique is testis-mediated gene transfer, where plasmid DNA-liposome complexes are injected into the testis (Chang et al 1999). We can reasonably expect that with the improvement of the transgenic technology rats will expand their usefulness to the pharmaceutical industry and fundamental research even more.…”
Section: Filipiak and Saunders 2006mentioning
confidence: 99%